Pengaruh Persepsi Mahasiswa, Motivasi, Ekspektasi Pendapatan Terhadap Pemilihan Karir Sebagai Profesi Akuntan - Sholaiha, Khusnatul; Nusantoro, Jawoto; Darmayanti, Elmira Febri (Universitas Muhammadiyah Metro, 2023)
This study aims to describe the influence of student perception, motivation, and income expectations on career selection in the accounting profession. The sampling technique in this study used purposive sampling techniques so that the samples obtained were 124 students. This study used a quantitative approach. The data was analyzed using the help of the SPSS 22 program with a type of analysis, namely multiple linear regression analysis. The results obtained from this study show that student perception, motivation, and income expectations have a significant effect on career selection as an accountant profession. The results of simultaneous testing of student perceptions, motivation, and income expectations together affect career selection as a student accountant profession of the S1 Accounting study program, Faculty of Economics and Business, University of Muhammadiyah Metro.